The war of nerves inside the Cold War mind - Sixsmith, Martin (Profile Books, 2021)
"More than any other conflict, the Cold War was fought on the battlefield of the human mind. Nearly thirty years since the collapse of the Soviet Union, its legacy still endures: not only in our politics, but in our own thoughts and fears. Drawing on a vast array of untapped archives and unseen sources, Martin Sixsmith vividly recreates the tensions and paranoia of the Cold War, framing it for the first time from a psychological perspective. Revisiting towering personalities like Khrushchev, Kennedy and Nixon, as well as the lives of the unknown millions who were caught up in the conflict, this is a gripping account of fear itself - one which is more resonant than ever today"--Publisher's description
Welcome collection
Keywords: Geschichte; Ost-West-Konflikt; Psychologische Kriegführung; USA; Sowjetunion; Cold War; Cold War / Psychological aspects; Cold War / Political aspects; War / Psychological aspects